Temple of the Sun and Court of the Moon, California World's Fair on San Francisco Bay (Stanley A. Plitz Company)
A graceful finger of white, this "Spire to the Sun" dominates the graceful architectural scheme of the Golden Gate International Exposition on Treasure Island in San Francisco Bay. Four hundred feet high, this spire competes in stature with the towers of the two Greatest Bridges in the world, Golden Gate and San Francisco-Oakland Bay Bridge.